Use of protocol and evaluation of postoperative residual curarization incidence in the absence of intraoperative acceleromyography - Randomized clinical trial - Santos,Filipe Nadir Caparica (2017)
Abstract Objective Evaluate the incidence of postoperative residual curarization (PORC) in the post-anesthesia care unit (PACU) after the use of protocol and absence of intraoperative acceleromyography (AMG). Methods Randomized clinical trial with 122 patients allocated into two groups (protocol and control). Protocol group received initial and additional doses of rocuronium (0.6 mg·kg-1 and 10 mg, respectively); the use of rocuronium was avoided in the final 45 min; blockade reversal with neostigmine (50 µg·kg-1); time ≥15 min between reversion and extubation. Control: initial and additional doses of rocuronium, blockade reversal, neostigmine dose, and extubation time, all at the discretion of the anesthesiologist. AMG was used in the PACU and PORC considered at T4/T1 ratio <1.0. Results The incidence of PORC was lower in protocol group than in control group (25% vs. 45.2%, p = 0.02). In control group, total dose of rocuronium was higher in patients with PORC than without PORC (0.43 vs. 0.35 mg·kg-1·h-1, p = 0.03) and the time interval between the last administration of rocuronium and neostigmine was lower (75.0 vs. 101.0 min, p < 0.01). In protocol group, there was no difference regarding the analyzed parameters (with PORC vs. without PORC). Considering the entire study population and the presence or absence of PORC, total dose of rocuronium was higher in patients with PORC (0.42 vs. 0.31 mg·kg-1·h-1, p = 0.01), while the time interval between the last administration of rocuronium and neostigmine was lower (72.5 vs. 99.0 min, p ≤ 0.01). Conclusion The proposed systematization reduced PORC incidence in PACU in the absence of intraoperative AMG.